1993
DOI: 10.1103/physrevlett.71.3850
|View full text |Cite
|
Sign up to set email alerts
|

How real are composite fermions?

Abstract: According to recent theories, a system of electrons at the half-filled Landau level can be transformed to an equivalent system of composite fermions at zero effective magnetic field. In order to test for these new particles, we have studied transport in antidot superlattices in a two-dimensional electron gas. At low magnetic fields electron transport exhibits well-known resonances at fields where the classical cyclotron orbit becomes commensurate with the antidot lattice. At v=y we observe the same dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
251
2
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(278 citation statements)
references
References 31 publications
23
251
2
2
Order By: Relevance
“…the same as for electrons. In the ballistic regime, the individual CF moves at the Fermi velocity and the average drift force e(v) x B~has negligible effect on the semiclassical motion of CFS near B~fi,consistent with experiments [10].…”
Section: Portions Of This Document May Be Illegible In Electronic Imasupporting
confidence: 67%
See 1 more Smart Citation
“…the same as for electrons. In the ballistic regime, the individual CF moves at the Fermi velocity and the average drift force e(v) x B~has negligible effect on the semiclassical motion of CFS near B~fi,consistent with experiments [10].…”
Section: Portions Of This Document May Be Illegible In Electronic Imasupporting
confidence: 67%
“…[9,10] Recently, the CF approach has been extended to edge states in the FQHE regime [11,12], which are all expected to propagate in the same direction as for the IQHE. To date few experiments have addressed the propagation direction of edge states.…”
Section: Portions Of This Document May Be Illegible In Electronic Imamentioning
confidence: 99%
“…A simple-minded way to think of this is as follows: References 29 and 30 take m* to be a constant, independent of B eff . But if m* diverges strongly enough where B eff = 0, both the effective potential energy term V eff given by equation (20) and the kinetic energy on the LHS of (19) should vanish where B eff = 0. Thus the upturn of ε near B eff = 0 that is predicted by the argument that is presented immediately below equation (20) (and occurs in the Hartree approximation) should not happen.…”
Section: Appendix: Comparison With Hartree Theories; Direction Of Promentioning
confidence: 99%
“…These remarkable predictions have been confirmed experimentally. 19,20,21 Working in the Corbino geometry, Jain demonstrated that composite fermion theory yields the experimentally observed fractionally quantized Hall conductances. His proof 11 was a generalization of the arguments that Laughlin 3 had used earlier to explain the integer quantum Hall effect.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of the CF concept is further supported by the determination of the CF Fermi wavevector [84,85] and the demonstration of the quasiclassical motion of composite fermions in their effective magnetic field * [86][87][88]. Cyclotron resonances of composite fermions have been measured directly by microwave absorption [89].…”
Section: The Composite Fermion Theorymentioning
confidence: 91%